My gran - Powell, Jillian; McClellan, Maddy (Mankato, Minn. : Sea-to-Sea : Distributed by Black Rabbit Books, 2010)
A child's unconventional grandmother enjoys bubble gum, fast motorbikes, pet rats, and nightclubs.
Keywords: Stories in rhyme; Grandmothers; Fiction